Look alive twenty-five [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2018)
There's nothing like a good deli and the Red River Deli in Trenton is one of the best. World famous for its pastrami, cole slaw and for its disappearing managers. Over the last month, three have vanished from the face of the earth; the only clue in each case is one shoe that's been left behind. The police are baffled. Lula is convinced that it's a case of alien abduction. Whatever it is, they'd better figure out what's going on before they lose their new manager, Ms. Stephanie Plum.